1994
DOI: 10.1002/cne.903470103
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of motoneurons supplying dorsal and ventral suboccipital muscles in the feline neck

Abstract: A combination of retrograde tracers was used to compare the relative distributions of motoneurons supplying the ventral and lateral suboccipital muscles, rectus capitis anterior (RCA), and rectus capitis lateralis (RCL), with those supplying dorsal muscles, including rectus capitis posterior muscles (RCP), complexus (CM), and the medial head of obliquus capitis superior (OCS). Three of the tracers, horseradish peroxidase, fluororuby, and fluorescein-conjugated dextran, were applied to cut nerve ends. Fast blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…This result is consistent with electrophysiological studies that reported monosynaptic connections between neurons in the LVN and premotor commissural interneurons and neck motoneurons (Wilson and Yoshida, 1969;Wilson and Maeda, 1974;Isu et al, 1988Isu et al, , 1990Uchino et al, 1988;Shinoda et al, 1994Shinoda et al, , 1997Sugiuchi et al, 1995). The somata and dendrites of these interneurons and motoneurons are located in areas of the ventral horn that are coincident with the termination zones of LVN neurons (Rose and Keirstead, 1988;Gordon and Richmond, 1991;Kitamura and Richmond, 1994;Suguichi et al, 1995). In addition, sparse projections were found ipsilaterally, in laminae IV to VII, and contralaterally, from lamina IV to IX (Holstege and Kuypers, 1982;Holstege, 1988;Rose et al, 1992).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…This result is consistent with electrophysiological studies that reported monosynaptic connections between neurons in the LVN and premotor commissural interneurons and neck motoneurons (Wilson and Yoshida, 1969;Wilson and Maeda, 1974;Isu et al, 1988Isu et al, , 1990Uchino et al, 1988;Shinoda et al, 1994Shinoda et al, , 1997Sugiuchi et al, 1995). The somata and dendrites of these interneurons and motoneurons are located in areas of the ventral horn that are coincident with the termination zones of LVN neurons (Rose and Keirstead, 1988;Gordon and Richmond, 1991;Kitamura and Richmond, 1994;Suguichi et al, 1995). In addition, sparse projections were found ipsilaterally, in laminae IV to VII, and contralaterally, from lamina IV to IX (Holstege and Kuypers, 1982;Holstege, 1988;Rose et al, 1992).…”
supporting
confidence: 92%
“…Some of these terminals may contact motoneurons innervating suboccipital flexor muscles, such as rectis capitis anterior major. These motoneurons are found on the medial wall of the ventral horn (Kitamura and Richmond, 1994) and stimulation of the utricular nerve evokes disynaptic EPSPs in these motoneurons (Ikegami et al, 1994). Other terminals of LVST axons in this region probably synapse on commissural and unidentified interneurons (Bolton et al, 1991;Sugiuchi et al, 1992Sugiuchi et al, , 1995Isu et al, 1996).…”
Section: Lvst and Mvst Projections From The Lvnmentioning
confidence: 98%
“…Perhaps it is unwise to propose any specific functional rationale to explain the motoneuronal distributions reported here and elsewhere (for further discussion, see Kitamura and Richmond, 1994). The identification of motoneuronal location, however, is a significant first step in the analysis of connectivity.…”
Section: Topography In the Cervical Spinal Cordmentioning
confidence: 83%
“…The motoneuron nuclei identified in the present study are compared with the motor nuclei identified in previous studies on the cervical cord. Distributions of motor nuclei of deep neck muscles in C1 come from Kitamura and Richmond (1994). Descriptions of motor nuclei in C4 and C6 are based on drawings from Sterling and Kuypers (1967), Richmond et al (1978), and Hentona (1993). cord.…”
Section: Rh and Lsmentioning
confidence: 99%
See 1 more Smart Citation